Bidirectional Associations between Bedtime Parenting and Infant Sleep: Parenting Quality, Parenting Practices, and their Interaction - Philbrook, Lauren E. (J Fam Psychol, 2016)
In keeping with transactional conceptualizations of infant sleep development (Sadeh et al., 2010), the present study examined longitudinal, bidirectional linkages between bedtime parenting (direct observations of parenting practices and quality) and infant sleep across the first six months postpartum. In doing so, we also drew from Darling and Steinberg's (1993) conceptual model to examine parenting quality as a moderator of linkages between specific bedtime practices and infant sleep. Multilevel model analyses revealed that the strongest increases in infant nighttime sleep across the first six months occurred among infants of mothers who engaged in low levels of nursing at bedtime. Within-person linkages between mothers' emotional availability (EA) at bedtime, infant distress, and infant sleep were found, such that at time points when mothers were more emotionally available, infants were less distressed and slept more throughout the night. Several moderating effects of maternal EA on linkages between parenting practices and infant sleep were obtained that were consistent with predictions from Darling and Steinberg (1993). Higher maternal EA in combination with less close contact at bedtime was associated with more infant sleep across the night on average, and higher EA in combination with fewer arousing bedtime activities predicted more rapid increases in infant sleep with age. Finally, there was evidence of infant-driven effects, as higher infant nighttime distress predicted lower EA at subsequent time points. Results showcased the complex, reciprocal interplay between parents and infants in the development of infant sleep patterns and parenting behavior during the first six months postpartum.